Personnel motivation of virtual organization - Uturytė-Vrubliauskienė, Laura; Merkevičius, Juozas (Business, Management and Economics Engineering, 2010)
Virtual organization is chosen as the analytical object. In order to develop organizations performance successfully, it is important to identify what type of factors motivate virtual employees. The research can be one of the ways to obtain detailed and reliable information necessary to identify means that motivate the employees in virtual organizations. The results of the research can help to develop good personnel motivation system of virtual organizations.The goal of this paper is to investigate the motivation tools that exist in virtual organiza-tions. In order to achieve this goal, the first part of the paper addresses for the analysis of the concepts of virtual organization, assumptions and circumstances for its development. Advantages and disadvantages of virtual organizations are described. The second part of the paper focuses on the research of personnel motivation in virtual organizations. First of all it describes the stages of research planning: formulation of research problem, objectives and tasks. Later the results of the research are presented and interpreted.Article in Lithuanian.Virtualiosios organizacijos personalo motyvavimas